Physicochemical characterization of the pulp of interspecific hybrids between Euterpe oleracea and Euterpe precatoria (Research, Society and Development, 2023)
The objective of this study was to physicochemically characterize pulp samples of interspecific hybrids between E. oleracea x E. precatoria, as well as to analyze the pulp yield and anthocyanin profile in the samples. The pulp yield for the hybrids studied was 34.63% for hybrid 1 and 24.42% for hybrid 2. Statistically significant differences were found between the two samples for the analysis of lipids, proteins and anthocyanins with the interspecific hybrid 2 presenting the highest levels for the aforementioned analyses. Regarding the anthocyanin profile, it was observed that hybrid 1 had a higher value of cyanidine 3-glucoside compared to rutinoside, contrary to what was observed for hybrid 2, which had a higher content of cyanidin 3-rutinoside. This indicates that between hybrids 1 and 2, there was a genetic predominance of E. oleracea for hybrid 1 and E. precatoria for hybrid 2, in relation to the anthocyanin profile.